Enhancing Family Health Management in Hypertensive Patients: A Case Study - Riansyah, Alvi; Permana, Gin Gin Sugih; Roslan Hidayat, Dian; Daniati, Eva (Nursing Case Insight Journal, 2026)
Hypertension is a highly serious non-communicable health problem. In the working area of the Tarogong Public Health Center, it ranks fifth among the top ten most prevalent diseases. This condition requires proper management to prevent adverse effects on the family's overall functions and roles. This study aims to describe the implementation of direct and comprehensive family nursing care for a family with a hypertensive member. This research uses a descriptive method with a case study approach focusing on one family (Mr. A's family, specifically Mrs. R) in the Tarogong Public Health Center's working area. Data collection techniques include interviews, observations, and physical examinations. Based on the assessment, the primary nursing problems identified were ineffective family health management and ineffective coping. After receiving nursing interventions for three days, the family demonstrated significant behavioral changes by modifying their lifestyle through the adoption of a low salt diet and actively utilizing healthcare facilities.The implementation of structured and comprehensive family nursing care has been proven to improve clinical outcomes and the client's quality of life by enhancing the family's independence in managing health problems